Evaluating the impact of the vaccination prescription program on herpes zoster vaccine coverage in Ningbo, China: An interrupted time series analysis - Jianmei Wang; Jiaxin Wang; Ning Li; Dongkai Du; Dandan Zhang; Rui Ma (Human Vaccines & Immunotherapeutics)
As the population ages, herpes zoster (HZ) and postherpetic neuralgia, which are associated with a substantial disease burden, are expected to increase. Ningbo began to implement the Vaccination Prescription Program for community individuals in April 2022. The anonymized HZ vaccination records of individuals aged above 50 during 2020–2023 were extracted from the Ningbo Immunization Information Management System. We applied interrupted time series analyses controlling for long-term trends and seasonality to assess the effects of the program on HZ vaccination coverage. Effect modification from demographic characteristics was investigated. Totally 18,133 doses of the HZ vaccine were administered. The cumulative coverage increased from 0.16‰ to 2.97‰, and the full series cumulative coverage from 0.04‰ to 2.48‰. Relatively higher coverage and full series coverage were observed among residents, females, individuals residing in inner districts and high socioeconomic regions, and those aged 50–59 years. During the transition period, a 468.7% increase in HZ vaccination coverage was evident (Rate Ratio [RR], 5.687; 95% Confidence Interval [CI], 2.334–13.857), and significant impact was detected among all demographic characteristics. During the post-implementation period, a 261.3% increase in coverage was evident (RR, 3.613; 95% CI, 1.202–10.858), while no effect was found among migrants, individuals living in regions with high socioeconomic status, and those aged above 70 years. Although the positive effect of the program, it is imperative to implement key strategies for providing affordable HZ vaccines, such as government funding, subsidies, and vaccination prescriptions from healthcare professionals, alongside peer initiatives and family members’ education.